Needs Analysis of Cosmetology Education Student Assessment Instrument on the Development of the Rasch Model Module - Mia Hafizah Tumangger; Ryzka Cahyaningrum (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Employing valid and reliable instruments aligned with the student population’s characteristics is essential. This study aimed to analyze the requirements of student assessment instruments in the Cosmetology Education study program to support the development of Rasch Model learning modules. The present study comprised 20 students enrolled in the cosmetology education program at Semarang University, who were selected based on purposive sampling. The research data were collected through observation, focus group discussions (FGDs), and documentation using observation sheets, FGD guides, and smartphones. The present study employed the stages of data analysis proposed by Miles and Huberman to analyze the research data obtained. The findings of the analysis demonstrated that the assessment instrument for cosmetology education students needs to be developed to support the Rasch Model module. It is anticipated that lecturers who wish to develop student assessment instruments will consider this research.